2022
DOI: 10.1016/j.envres.2021.112614
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 seasonality in temperate countries

Abstract: Introduction While the beneficial effect of vaccination, restrictive measures, and social distancing in reducing mortality due to SARS-CoV-2 is intuitive and taken for granted, seasonality (predictable fluctuation or pattern that recurs or repeats over a one-year period) is still poorly understood and insufficiently taken into consideration. We aimed to examine SARS-CoV-2 seasonality in countries with temperate climate. Methods We identified countries with temperate cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 22 publications
3
21
0
Order By: Relevance
“…Like for other temperate countries, in Romania and its capital Bucharest, there is a linkage between climate variables seasonality and direct impacts on COVID-19 viral infection seasonality. This result was demonstrated also by other studies ( D'Amico et al, 2022 ; Zoran et al, 2022 ).…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Like for other temperate countries, in Romania and its capital Bucharest, there is a linkage between climate variables seasonality and direct impacts on COVID-19 viral infection seasonality. This result was demonstrated also by other studies ( D'Amico et al, 2022 ; Zoran et al, 2022 ).…”
Section: Resultssupporting
confidence: 88%
“…Also this study found significant anticorrelations between daily average Planetary Boundary Layer heights over Bucharest city and daily new COVID-19 confirmed cases and mortality as follows: rDNC = −0.53, p < 0.01 and respectively rDND = −0.57, p < 0.01. High levels of daily PBL of (1607.19 ± 526.06) m registered during the first COVID-19 wave in Romania may explain the low severity of the first COVID-19 wave in Bucharest city in comparison with the rest of some European metropolitan cities ( D'Amico et al, 2022 ; Zoran et al, 2020a ; Zoran et al, 2020b ; Zoran et al, 2021 ). An opposite situation was recorded during the second, and the fourth COVID-19 waves when the daily average PBL heights recorded abnormally low values per each wave and season, being respectively of (538.74 ± 293.26) m, and (920.23 ± 603.25) m, that can explain high rates of infectivity and deaths in Bucharest city.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Lastly, seasonality played a role in the trajectory of the pandemic during the first wave of COVID-19 in Italy [ 67 , 68 ]. Italy presents differences in terms of temperature and humidity throughout the peninsula, but since the entire country is within the Northern Tropic and more precisely the Mediterranean area, we omitted the seasonal component at a regional level in line with other studies [36] .…”
Section: Discussionmentioning
confidence: 99%
“…Along this line of research, remarkable are the studies of D’Amico et al who used a multivariate regression to assess the influence of temperatures and vaccinations on mortality rates in temperate climate countries. They found a negative correlation with temperatures and discovered that the vaccination’s effect grew larger as the temperature decreased 4. Similarly, Ma et al studied the problem in the USA using a generalised additive mixed model.…”
Section: Introductionmentioning
confidence: 99%